2016
DOI: 10.1158/0008-5472.can-15-3118
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin-like Protein FAT10 Stabilizes eEF1A1 Expression to Promote Tumor Proliferation in a Complex Manner

Abstract: Human HLA-F adjacent transcript 10 (FAT10) is the only ubiquitin-like protein that can directly target substrates for degradation by proteasomes, but it can also stabilize the expression of certain substrates by antagonizing ubiquitination, through mechanisms as yet uncharacterized. In this study, we show how FAT10 stabilizes the translation elongation factor eEF1A1, which contributes to cancer cell proliferation. FAT10 overexpression increased expression of eEF1A1, which was sufficient to promote proliferatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 60 publications
(69 citation statements)
references
References 44 publications
6
63
0
Order By: Relevance
“…Recently, we showed for the first time that FAT10 stabilized substrate expression by inhibiting ubiquitination of the substrate [13]. In that study, we demonstrated that FAT10 and Ub competitively bound to the substrate to form FAT10- and Ub-substrate complexes; FAT10 overexpression decreased Ub-substrate complex levels and increased FAT10-substrate complex levels [12]. In this study, we provide evidence that FAT10 also stabilizes Survivin and thus increases Survivin expression in BC cells.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Recently, we showed for the first time that FAT10 stabilized substrate expression by inhibiting ubiquitination of the substrate [13]. In that study, we demonstrated that FAT10 and Ub competitively bound to the substrate to form FAT10- and Ub-substrate complexes; FAT10 overexpression decreased Ub-substrate complex levels and increased FAT10-substrate complex levels [12]. In this study, we provide evidence that FAT10 also stabilizes Survivin and thus increases Survivin expression in BC cells.…”
Section: Discussionsupporting
confidence: 55%
“…We previously found that FAT10 stabilizes substrates by competing with ubiquitin (Ub) for binding, ultimately decreasing substrate ubiquitination [12, 13]. Thus, we hypothesized that competition between FAT10 and Ub for Survivin binding decreases the ubiquitination and degradation of Survivin in BC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of FAT10 have mainly focused on its substrate‐degrading function . We previously reported that FAT10 can stabilize its substrate to promote the progression of tumors, including HCC . We found that FAT10 stabilizes β‐catenin protein by inhibiting its ubiquitination and degradation, thus promoting HCC cell invasion and metastasis .…”
mentioning
confidence: 90%
“…Recently, multiple studies have found that abnormal FAT10 expression is closely related to the occurrence and development of tumors. FAT10 is highly expressed in various tumors, including hepatocellular carcinoma (HCC), and closely related to tumor proliferation, invasion and metastasis, and prognosis . Therefore, FAT10 is considered an oncogene.…”
mentioning
confidence: 99%